2003
DOI: 10.1530/eje.0.1490007
|View full text |Cite
|
Sign up to set email alerts
|

Role of gamma probes in performing minimally invasive parathyroidectomy in patients with primary hyperparathyroidism: optimization of preoperative and intraoperative procedures

Abstract: Objective: In the last decade, surgery of primary hyperparathyroidism (HPT) due to a solitary adenoma has moved on from the traditional wide bilateral neck exploration (BNE) to more limited approaches such as unilateral neck exploration and minimally invasive parathyroidectomy. Design: To define the role of intraoperative gamma probe and injection of a low 99m Tc-MIBI dose in performing minimally invasive radio-guided surgery (MIRS) in HPT patients with a solitary parathyroid adenoma. Methods: From September 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 26 publications
2
45
0
3
Order By: Relevance
“…Rubello et al (14) performed minimally invasive radioguided surgery in preselected patients with primary HPT with a success rate of 97.9%. Using a hand-held gamma collimated probe, which was inserted through a 2 -2.5 cm skin incision, even ectopic PTG adenoma in the upper mediastinum and at the carotid bifurcation, as well as glands deep in the para-oesophageal/ para-tracheal space, was rapidly found (14). In a prospective series by Nichol et al (16), radio-guided surgery for secondary and tertiary HPT was associated with a cure rate of 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Rubello et al (14) performed minimally invasive radioguided surgery in preselected patients with primary HPT with a success rate of 97.9%. Using a hand-held gamma collimated probe, which was inserted through a 2 -2.5 cm skin incision, even ectopic PTG adenoma in the upper mediastinum and at the carotid bifurcation, as well as glands deep in the para-oesophageal/ para-tracheal space, was rapidly found (14). In a prospective series by Nichol et al (16), radio-guided surgery for secondary and tertiary HPT was associated with a cure rate of 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, to confirm the identification and removal of the hyperfunctional parathyroid it is accepted as adequate an ex vivo radioactivity count of the adenoma 20% or 40% greater than the value of the postexcisional background radioactivity, in association or not with intraoperative measurement of PTH, depending on the protocols (10,11). Furthermore, according to some authors, the count of radioactivity is so reliable as to make unnecessary the intraoperative PTH assay or other confirmatory examinations (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Other authors described a separate day protocol whereas preoperative double-tracer (Tc99 m -pertechnetate and Tc99 m -sestaMIBI) subtraction scintigrafy is performed several days before the surgery to identify the adenoma (4). On the day of the surgery, some minutes before the beginning of the operation, patients are injected with low dose of Tc99 m -sestaMIBI (37 MBq) (6 radiation due to radiotracer uptake of the surrounding tissues, above all thyroid parenchyma.…”
Section: Introductionmentioning
confidence: 99%
“…2,[6][7][8][9][10] Improvements in preoperative parathyroid imaging (using computed tomography, magnetic resonance imaging, and sestamibi scans), the development of the intraoperative handheld gamma probe, and intact parathyroid hormone (PTH) assays served as an impetus for minimally invasive parathyroidectomy (MIP). Various studies have shown that MIP can be successfully performed with preoperative sestamibi scanning and intraoperative radioguidance 1,6,[11][12][13][14] without the need to measure PTH levels. 1,5,11,14 Advantages of MIP include decreased disruption of normal tissue, smaller incisions, reduced operative times, the option of performing the procedure under local anesthesia, lower complication rates and hospital costs, and same-day discharge.…”
mentioning
confidence: 99%
“…Various studies have shown that MIP can be successfully performed with preoperative sestamibi scanning and intraoperative radioguidance 1,6,[11][12][13][14] without the need to measure PTH levels. 1,5,11,14 Advantages of MIP include decreased disruption of normal tissue, smaller incisions, reduced operative times, the option of performing the procedure under local anesthesia, lower complication rates and hospital costs, and same-day discharge. 2,3,6,11,15 Many investigators have demonstrated cure rates of greater than 90% in appropriately selected patients.…”
mentioning
confidence: 99%